Pengaruh Pemberian Dosis Pupuk Biourin Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Putih (Brassica chinensis L.) - Albertus Agung Neno (Agriculture Faculty of Flores University, 2020)
This study aims to determine the effect of Biourine fertilizer dosage on the growth and production of chicory and to determine the optimum dose of Biourine fertilizer in increasing growth and yield of chicory is BU0 0, litre/ha (control) BU1, 4000 liters/ha or equivalent to 2. ltr / plot BU2, 8000 litres / ha or equivalent to 4 ltr / plot BU3,12,000 litres / ha or equivalent to 6 litres / plot BU4.16,000 litres / ha or the equivalent of 8 ltr / plot. The observation variable of plant height growth was 0.94%, the total average number of leaves was 3.48%, the total average crop diameter was 2.51%, the total average fresh weight of ton-1 stover was 2.23%. , the total average fresh weight of stover ha-1 was 2.23%. The results of this study indicate that dosing of biourine fertilizer can increase the percentage of growth and yield of chicory (Brassica Chinensis L), namely plant height of 0.94%, number of leaves by 3.48%, crop diameter of 2.51%, fresh weight. cropping was 2.23% and fresh weight per hectare was 2.23%. The optimum dose of biourine fertilizer for the best chicory plants in increasing the growth of chicory is 16,000 litres / ha which gives a plant height growth of 24.47 cm, the number of leaves is 14.35, crop diameter is 13.95 cm, fresh weight of stover. plants amounted to 486.25 grams/plant and 475.40 grams/plant, the fresh weight of plant stover per hectare was 19.45 tons/ha and 19.02 tons/ha.